Risk of cancer in relatives of patients with myotonic dystrophy: a population‐based cohort study. (17th May 2014) - Lund, M.; Diaz, L. J.; Gørtz, S.; Feenstra, B.; Duno, M.; Juncker, I.; Eiberg, H.; Vissing, J.; Wohlfahrt, J.; Melbye, M.
<x xml:space="preserve">Abstract</x> Background and purpose Myotonic dystrophies (DM) are autosomal dominantly inherited neuromuscular disorders caused by unstable nucleotide repeat expansions. DM and cancer have been associated, but the pathogenesis behind the association remains unclear. It could relate to derived effects of the DM genotype in which case non‐DM relatives of DM patients would not be expected to be at increased risk of cancer. To elucidate this, a population‐based cohort study investigating risk of cancer in relatives of DM patients was conducted. Methods DM was identified using the National Danish Patient Registry and results of genetic testing. Information on cancer was obtained from the Danish Cancer Registry. A population‐based cohort of 5 757 565 individuals with at least one relative was established using the Danish Family Relations Database based on kinship links in the Danish Civil Registration System. Familial aggregation of cancer was evaluated by (incidence) rate ratios (RRs) comparing the rate of cancer amongst relatives of patients with DM from 1977 to 2010 (exposed) with the rate of cancer amongst persons with a relative of the same type but without DM (non‐exposed). Results In first‐degree relatives of individuals with DM the adjusted RR of cancer was 0.89 (95% confidence interval 0.71–1.12) overall, and in stratified analyses 0.68 (0.37–1.12) before age 50 and 0.96 (0.74–1.23) at age 50 or older. Conclusions The present study does not support an increased risk of cancer in non‐DM relatives of DM patients suggesting that cancer and DM are associated through derived effects of the DM genotype.